Synopsis of Aenictus species groups and revision of the A. currax and A. laeviceps groups in the eastern Oriental, Indo-Australian, and Australasian regions (Hymenoptera: Formicidae: Aenictinae) - Jaitrong, Weeyawat; Yamane, Seiki (Zootaxa, 2011)
Twelve species groups are established in the ant genus Aenictus of the eastern part of Oriental region, and Indo-Australian and Australasian regions, and the species of the Aenictus currax group and A. laeviceps group are revised. Nine species (six named and three new species) of the A. currax group occurring in this area are: A. cornutus Forel, A. currax Emery, A. diclops Shattuck, A. glabrinotum Jaitrong et Yamane, sp. nov., A. gracilis Emery, A. huonicus Wilson, A. parahuonicus Jaitrong et Yamane, sp. nov., A. pfeifferi Zettel et Sorger, and A. wayani Jaitrong et Yamane, sp. nov. Thirteen species (six named and seven new species) are recognized in the A. laeviceps group: A. alticola Wheeler et Chapman, A. binghami Forel, A. bodongjaya Jaitrong et Yamane, sp. nov., A. breviceps Forel, stat. nov., A. brevinodus Jaitrong et Yamane, sp. nov., A. fulvus Jaitrong et Yamane, sp. nov., A. hodgsoni Forel, A. laeviceps (F. Smith), A. luzoni Wheeler et Chapman, A. montivagus Jaitrong et Yamane, sp. nov., A. rotundicollis Jaitrong et Yamane, sp. nov., A. siamensis Jaitrong et Yamane, sp. nov., and A. sonchaengi Jaitrong et Yamane, sp. nov. A. fergusoni var. breviceps Forel is removed from synonymy with A. laeviceps and raised to full species. Lectotypes and paralectotyps are designated for A. alticola, A. binghami, A. breviceps, A. cornutus, A. currax, A. gracilis, A. laeviceps, and A. luzoni.